2021
DOI: 10.1016/j.apcatb.2021.120143
|View full text |Cite
|
Sign up to set email alerts
|

Single-route delaminated clay composites for efficient visible-light photo-mineralization of antibiotic-resistant bacteria and associated genes in water

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 83 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…No bacterial regrowth was observed in treated water stored in the light/dark for 7 days. 104 DPC was also explored for photo-disinfection of the fluoroquinolone-resistant genes parE and gyrB, and it was shown to significantly reduce the amount of these genes present. DPC proved to be a stable photocatalyst as it was tested over 7 months and it gave optimal results, showing it to have the potential for commercialization.…”
Section: Cps-based Composites For Microbial Contaminant Removalmentioning
confidence: 99%
“…No bacterial regrowth was observed in treated water stored in the light/dark for 7 days. 104 DPC was also explored for photo-disinfection of the fluoroquinolone-resistant genes parE and gyrB, and it was shown to significantly reduce the amount of these genes present. DPC proved to be a stable photocatalyst as it was tested over 7 months and it gave optimal results, showing it to have the potential for commercialization.…”
Section: Cps-based Composites For Microbial Contaminant Removalmentioning
confidence: 99%
“…One of the advantages of using clay materials in removal processes is that it is an economical material with a high capacity to remove organic and inorganic pollutants [90]. One of its important characteristics, in addition to being one of the more abundant adsorbents in nature, is that it has a high ion exchange capacity, high specific surface area, and good colloidal dispersion, making these materials good for the treatment of wastewater containing organic and inorganic compounds, among others [91][92][93].…”
Section: Claysmentioning
confidence: 99%
“…In recent years, natural layered clay minerals have been widely used as catalyst carriers because of their excellent carrier effects (cocatalysis, codispersion, and cosorption). Nanoclays have obtained extensive attention in the defect regulation of nanomaterials due to their unique structure and abundant surface hydroxyl groups (silicon and/or aluminum hydroxyl groups) . Our previous work found that Al–OH on the kaolinite surface plays a pivotal role in regulating the amount of oxygen vacancy and Co 2+ on the Co 3 O 4 surface; the hydroxyl group of kaolinite can react with intermediate groups to form defective g-C 3 N 4 and the modulation of defects can be achieved by changing the number of hydroxyl groups .…”
Section: Introductionmentioning
confidence: 99%